Ragam Gaya Arsitektur Bangunan Rumah Tinggal di Surakarta Tahun 1745-1930 - Yuandhi Yuan Pratama; Tri Yuniyanto (Jurnal Artefak, 2026)
The diversity of historic buildings in Surakarta offers a fresh topic for historical research to illustrate past cultures. This study aims to analyze the variety of architectural styles of residential buildings in Surakarta from 1745 to 1930, covering the transition from the purely traditional era to the influence of colonial modernity. The method employed is the historical method, beginning with heuristics, verification, interpretation, and historiography. This study utilizes interdisciplinary approaches within architecture as a supporting methodology, specifically visual analysis of architectural artifacts in the form of photographic archives. The research findings indicate that during the 1745–1930 period, residential architecture in the city of Surakarta was dominated by traditional Javanese architecture, with each type distributed across areas influenced by the Javanese cosmological concept of kuthanagara, such as Joglo, limasan, kampung, and panggang-pe. European architecture is evident in the use of the Indische Empire style, which has undergone degradation, while Chinese architecture is evident in shop-house buildings as a measure of economic efficiency. This research can serve as a reference for the development of urban history or local history materials using an interdisciplinary learning approach, thereby serving as an effort to increase students’ interest in learning.